The natural course of pT2 prostate cancer with positive surgical margin: predicting biochemical recurrence - Karl, A.; Buchner, A.; Tympner, C.; Kirchner, T.; Ganswindt, U.; Belka, C.; Ganzer, R.; Burger, M.; Eder, F.; Hofstädter, F.; Schilling, D.; Sievert, K.; et al. (World Journal of Urology, 2015)
To predict biochemical recurrence respecting the natural course of pT2 prostate cancer with positive surgical margin (R1) and no adjuvant/neoadjuvant therapy.A multicenter data analysis of 956 patients with pT2R1N0/Nx tumors was performed. Patients underwent radical prostatectomy between 1994 and 2009. No patients received neoadjuvant or adjuvant therapy. All prostate specimens were re-evaluated according to a well-defined protocol. The association of pathological and clinical features, in regard to BCR, was calculated using various statistical tests.With a mean follow-up of 48 months, BCR was found in 25.4 %. In univariate analysis, multiple parameters such as tumor volume, PSA, Gleason at positive margin were significantly associated with BCR. However, in multivariate analysis, Gleason score (GS) of the prostatectomy specimen was the only significant parameter for BCR. Median time to recurrence for GS <= 6 was not reached; 5-year BCR-free survival was 82 %; and they were 127 months and 72 % for GS 3+4, 56 months and 54 % for GS 4 + 3, and 27 months and 32 % for GS 8-10. The retrospective approach is a limitation of our study.Our study provides data on the BCR in pT2R1-PCa without adjuvant/neoadjuvant therapy and thus a rationale for an individual's risk stratification. The data support patients and physicians in estimating the individual risk and timing of BCR and thus serve to personalize the management in pT2R1-PCa.
EVALuna2:6640